CY-Handee Rubber Mouldings Sdn Bhd: The Fluctuating Company’s Profit Margin - A Case Study - Tan, Hui Huang (2014)
CY-Handee (CYH) Rubber Mouldings Sdn Bhd is currently one of the major exporters of rubber bathmat in the world. The company has been focusing on the design, manufacture and marketing of bathroom suction mats. In recent years, CYH has been experiencing fluctuating in profit margin making it a perfect choice as a case study. This case focuses on identifying factors that affect CYH‟s fluctuating profit margin. In-depth interviews were carried out with seven subjects from CYH to find out the issues and challenges in the aspect of production, marketing and management as well as the customer requirements in rubber bathmat industry.